Management of Tahfiz Learning for Students of Taman Pendidikan Qur’an (TPQ) Al-Islamiyyah Bengkalis - Afrizan, Zul; Yanti, Seppy; Khairi, Muhammad Afizul; Arrasyidi, Roisul Umam (ALSYS, 2025)
This study investigates the management of Tahfiz learning at the Qur’an Education Park (Taman Pendidikan Qur’an, TPQ) Al-Islamiyyah Bengkalis, addressing the critical need for effective non-formal Islamic education institutions that nurture young Muslim generations. Employing a qualitative descriptive approach, the research examines managerial strategies and challenges in administering the Tahfiz program. Data were collected through observation, in-depth interviews, and document analysis. Findings reveal that TPQ Al-Islamiyyah implements a systematic and adaptive management framework encompassing planning, implementation, and evaluation phases, reinforced by active parental and community engagement. Key strategies include a structured curriculum design, flexible learning schedules, targeted memorization techniques such as talaqqi and tikrar, and continuous teacher development via internal training programs. The study underscores that sustainable success in Tahfiz education depends on integrated collaboration among educators, parents, and the wider community, highlighting the importance of ongoing innovation and responsiveness to students’ social contexts. These insights contribute both practical guidance and theoretical advancement for managing non-formal Tahfiz education institutions effectively.